Content validation of common measures of functioning for young children against the International Classification of Functioning, Disability and Health and Code and Core Sets relevant to neurodevelopmental conditions - D’Arcy, Emily; Wallace, K.; Chamberlain, Angela; Evans, Kiah; Milbourn, Ben; Bolte, Sven; Whitehouse, A.J.O.; Girdler, Sonya (SAGE PUBLICATIONS LTD, 2021)
Content validity describes the extent to which a measure represents, and is relevant to, the construct it aims to assess. The International Classification of Functioning, Disability and Health and derived Core/Code Sets (Sets) for autism, attention deficit-hyperactivity disorder, cerebral palsy and early developmental delay and disability are adequate to establish the content validity of measures aiming to assess functioning in young children with neurodevelopmental conditions (NDCs). This article aimed to assess the content validity of comprehensive assessments of functioning for young children with NDCs against these standards. Twenty-two common measures of functioning were evaluated for content validity against the International Classification of Functioning, Disability and Health at a domain level, with 10 measures analysed at the item-level and compared to the Sets relevant to young children with NDCs. Measures covered between 21% and 57% of the combined Set codes and 19% to 63% of codes from specific Sets. Much of this variation was between measures, with some variation due to differences between individual Sets. The percentages reflect that measures heavily focus on activities and participation areas, with environmental factors rarely assessed. These findings are useful for clinicians, policymakers, and researchers in identifying the most appropriate measures for assessing functioning in young children with neurodevelopmental conditions. Lay abstract: Young children who have developmental delay, autism, or other neurodevelopmental conditions can have difficulties doing things in different areas of their life. What they can and cannot do is called their level of functioning. There are lots of assessment measures that aim to assess functioning. But, we are not sure if these measures assess all the things we need to know about these children’s functioning. Other research has identified lists of items (codes) that need to be assessed to understand functioning for young children with different neurodevelopmental conditions fully. These lists include body functions (the things a child’s body or brain can do), activities and participation (the activities and tasks a child does) and environmental factors (parts of the environment that can influence functioning). In this study, we looked at the items from these lists assessed by different functioning measures to see how they compared to what should be assessed. The measures that we looked at covered 21%–57% of all the codes and 19%–63% of the codes for lists specific to different conditions. Most of the measures focused on activity and participation codes, and they rarely assessed environmental factors. Knowing which codes and how much of the lists the measures assess can help researchers, clinicians and policymakers to choose measures that are more appropriate for young children with neurodevelopmental conditions.